Development Of Cinema Therapy Technique Media Literacy Services Based On The Gagne Model To Anticipate Free Association: Pengembangan Media Literasi Teknik Sinema Terapi dalam Layanan BK Berbasis Model Gagne Untuk Mengantisipasi Pergaulan Bebas - Frezy Paputungan (LPPM Universitas Bina Mandiri Gorontalo, 2023)
This study aims to describe the initial conditions of media literacy using cinema therapy techniques to anticipate free association among students at SMK Negeri 1 Lolayan, Bolaang Mongondow Regency, to create a guidebook for the use of cinema therapy technique media literacy in Guidance and Counseling services based on the Gagne model to anticipate promiscuity among students of SMK Negeri 1 Lolayan and knowing the steps for developing and effectiveness of media literacy using cinema therapy techniques to anticipate free association among students of SMK Negeri 1 Lolayan, Bolaang Mongondow Regency. This research approach is a type of research development or Research and Development (R&D). The data used is qualitative data. Based on the data analysis performed, the results of the post-test showed that 26 students completed promiscuity problems with a mastery proportion of 86.6%. Of these proportions, media literacy using cinema therapy techniques is said to be effective.